The Effectiveness of Mnemonic Keyword Method to Improve Students' Vocabulary Mastery at The First Year of SMP Negeri 12 Parepare - Mutmainnah Nasri (Institut Agama Islam Negeri Parepare, 2021)
This script was conducted to examine in teaching vocabulary by using the mnemonic keyword method in improving students’ vocabulary mastery at first-year SMP Negeri 12 Parepare. This script used a quasi-experimental design. The population of this script was class VII at SMP Negeri 12 Parepare that comprises 103 students. The writer had chosen two classes as the sample by using a purposive sampling technique, one class as an experimental class and one class as the control class where quantity is 50 samples, 25 students in the experimental class and 25 students in the control class. The research findings show that there are significant differences in vocabulary mastery between students who are taught using the mnemonic keyword method and those who are not taught by using these methods in the first year of SMP Negeri 12 Parepare. This can be seen from the result show that the t-test value of the experimental class (13,05) was greater than the t-test value of the control class (9,03) it means that the alternative hypothesis (Ha) concluded that the mnemonic keyword can improve vocabulary mastery students’.It was concluded that the null hypothesis (H0) was rejected. And also, it can be seen from the average pre-test and post-test scores in the experimental class that is 57,44 and 76,88 (19,44) while the pre-test and post-test average score in the control class are 58,08 and 72,8 (14,72) with a large value of the treatment are 4,72. It can be concluded that the mnemonic keyword method is an effective method that can be used in teaching vocabulary mastery learning.